Performance in solving algebraic problems of students using cooperative learning strategies - Diaz, Earl Rodson Y.; Irorita, Angelo P. and Ragos, Nicasto Exequiel II B. 4 0 16; 5 (2016)
ABSTRACT: The purpose of the study is to improve the performance of students in solving algebraic problems through the use of cooperative learning methods. The researchers applied cooperative learning strategies to improve the student's level of performance. Data gathered are in the form of pre-test. These exams scores are used in order to measure the level of performance of the students; also, the researchers prepared supporting activities to empower the strategy. The results suggest that students tend to learn more in groups. The level of performance of the students improved after the use of cooperative learning strategy.
Thesis: (Bachelor of of Secondary Education with Specialization in Mathematics) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2